Kajian Literatur: Faktor-Faktor Penyebab Kejadian Dissociative Trance Disorder pada Pelajar - Ridho, Fiki Muhammad (Penerbit Goodwood, 2023)
Purpose: This study aims to find out more about the factors that cause Dissociative Trance Disorder (DTD) in students. Research methodology: This research method is a literature review through the collection of secondary data from the Google Scholar database with keywords: factor, Dissociative Trance Disorder, and student, publication between 2012-2022, full text, and open access. Results: The results of this study show that several stressor factors cause DTD, including changes in study habits, the learning process, a new learning environment, relationships with teachers, relationships with friends, conflicting relationships with parents, girlfriend or boyfriend, low academic achievement, financial problems, academic demands from parents, physical exhaustion, harsh parenting styles, childhood violence, introverted personality, and anxiety. The learning process is the biggest stressor for students because 59.7% of DTD cases occur during the learning process. Conclusions: Some stress factors that cause DTD include changes in learning habits, new learning environments, learning processes, relationships with teachers, relationships between fellow students, relationship problems with parents, low academic achievement, academic demands from parents, problems with boyfriends, financial problems, harsh parenting styles, physical exhaustion, violence in childhood, introverted personalities, and anxiety. Limitations: The limitation of this study is that it only uses the literature review method which has weaknesses in the data studied. Suggestions from researchers for further research are that further research can be carried out with other, more rigorous research methodologies to explore that cause DTD, and more research is needed to compare DTD with other dissociative disorders that occur among students. Contribution: This research is expected to increase understanding, knowledge, and insight about the phenomenon of the occurrence of DTD or possession in students at school that in fact DTD occurs due to various internal and external factors.